Implementasi Kurikulum 2013 dalam Pembinaan Karakter Siswa Kelas IX A di MTs Hidayatul Mubtadiin Lampung Selatan - Yanwari Yanwari; Muhammad Feri Fernadi; Eka Tusyana (Journal on Education, 2023)
This study aims to describe the implementation steps of the 2013 curriculum in fostering student character. To explain the constraints of implementing the 2013 curriculum in fostering student character. To explain the implications of implementing the 2013 curriculum in fostering student character at MTs Hidayatul Mubtadiin. The data collection technique used is the observation of the participation value or its constraints. Oral history interviews, structured and unstructured interviews. Documentary studies or documentation. Data analysis techniques use data collection, data reduction, data presentation, drawing conclusions. The results of the 2013 curriculum implementation research in fostering student character at MTs Hidayatul Mubtadiin show that the steps for implementing the 2013 curriculum in fostering student character are that a teacher attends curriculum 2013 training, attends workshops on 2013 curriculum materials. the teacher makes a lesson plan before the learning takes place and uses a variety of methods. The obstacles to the implementation of the 2013 curriculum in fostering the character of students at MTs Hidayatul Mubtadiin are related to the lack of facilities, including the lack of places for worship, places for ablution, libraries. 3). Implications or positive impacts of government policies in the implementation of the 2013 curriculum at MTs Hidayatul Mubtadiin, namely 3S habituation, scouting, local content, attitude strengthening the ten cultures of shame, parenting. Meanwhile, the implications or negative impacts of government policies in the implementation of the 2013 curriculum at MTs Hidayatul Mubtadiin are burdensome for students because the hours of study are added even though students have a maximum limit of concentration in learning, teacher preparation takes a long time. Not just one or two training sessions, and too many hours.